Tourism Specialization and Sustainability: A Long-Run Policy Analysis - Fabio Cerina (Fondazione Eni Enrico Mattei (FEEM), 2006)
This study focuses on the dynamic evolution of a small open economy specialized in tourism based on natural resources when tourist services are supplied to foreign tourists who are crowding-averse and give positive value to the environmental quality. We analyse the steady-state properties and run several policy exercises in two versions of our model: in the first, private agents income is spent entirely on consumption while, in the second, agents are allowed to invest part of their income in pollution abatement technology (PAT) which artificially increases the rate of regeneration of the environmental asset. A unique locally saddle point equilibrium is found in both versions and for both the market and the centralized solution. Our main findings are that: 1) a corrective income tax raises steady state utility in both versions but is capable of leading the economy in its first-best dynamic path only when agents cannot invest in the PAT; 2) when the PAT is available to the government but not to agents, an income tax which finances abatement expenditures may increase steady state utility with respect to the market solution when the natural regeneration rate of the environment and the degree of crowding-aversion are both low enough; 3) when PAT is available, the market chooses to devote a higher fraction of income to abatement than the central planner but in both cases this fraction is positive only if the natural rate of regeneration is not too large; 4) when PAT is available an income pollution tax does not affect the dynamic path of the market economy.
Keywords: L83; O41; Q26; Q56; 330; Tourism specialization; Sustainability; Environmental quality; Crowding; Pollution abatement; Tourismusökonomie; Kleines-offenes-Land; Umweltbelastung; Nachhaltige Entwicklung; Theorie